An evaluation of people’s knowledge of adult vaccination information level and attitudes during the pandemic Era - Kıskaç,Neşe (2021)
SUMMARY OBJECTIVE: This research was carried out to evaluate people’s knowledge of adult vaccination and their attitude and to observe the effect of the pandemic era on this situation. METHODS: A total of 1,425 people (18–80 years old) were included in this study. The types of questions like the province where they live, age, gender, occupation, education status, and the presence of chronic diseases, as well as knowing which vaccines are used in adult vaccination, which of these vaccines they had in the last 10 years, which ones they plan to have this year, and whether COVID-19 pandemic changed their perspective on adult vaccinations or not were asked to people. RESULTS: In the last 10 years, while participants stated that they had the highest rate of tetanus vaccine with 29.8%, hepatitis B vaccine with 23.1%, influenza vaccine with 22.7%, human papillomavirus vaccine with 1.3%, and zoster vaccine with 0.3% were the lowest levels of vaccines. CONCLUSIONS: As a result, it seems that we are far from the goals set by the health authorities for adult vaccination. We observed that the COVID-19 pandemic raised awareness toward pneumococcus and influenza vaccines and interest toward adult vaccinations and at the same time changed the thoughts against adult vaccinations.